Research on Automated Detection of Sensitive Information Based on BERT. Issue 1 (January 2021) - Ding, Meng; Wang, Xing; Wu, Changming; Wang, Kaixuan; Yang, Xue
Abstract: With the booming of the Internet, Web public opinion plays an increasingly important role in the stability of the network community. Therefore, the sensitive information hidden on the Internet is likely to lead to unpredictable social impact. This paper focuses on the detection of Chinese sensitive information. First, we build a corpus to train the detection model. Secondly, we apply the Bert method to the detection problem. Then, many popular NLP methods are applied to this problem to show the progress of Bert in a sensitive information detection task. Finally, we got a sensitive information detection model based on BERT with a high F1 score of 97.31.